Phytosociological and phytogeographic characterization of a riparian forest sector in alfredo wagner, santa catarina state, as subsidy for ecological restoration Caracterização fitossociológica e fitogeográfica de um trecho de floresta ciliar em alfredo wagner, sc, como subsídio para restauração ecológica - Negrini M.* (2013)
The understanding of floristic and structure of tree communities is essential to subside the strategies of forest restoration. In this sense, a phyto-sociological survey was conducted in a forest fragment situate along a tributary of Caeté river, in Alfredo Wagner, state of Santa Catarina, in order to: i) know the structure of trees and flora in this forest, ii) classify the species found according to ecological groups and iii) compare the flora of the study area with other studies in Araucaria forest (FOM), Atlantic Rain Forest (FOD) and the transition area between FOM-FOD of Santa Catarina state. In this fragment, 10 plots of 400 m2 were allocated, where all individual trees with the circumference at breast height (CBH, measured at 1.30 m above the ground) greater than or equal to 15.7 cm were measured, marked and identified. The species were classified into the following succession groups: pioneer, climax light-demanding or climax shade-tolerant. The Rectified Correspondence Analysis (DCA) was used for the floristic comparison. The structure of the tree component was described by the density, frequency, dominance and importance value (VI). The results showed elevated species richness (98 species). It was found typical species of FOM, such as Araucaria angustifolia (Bert.) Kuntze, and species characteristics of FOD such as Byrsonima ligustrifolia A.Juss., confirming the study fragment as an area of ecological tension between FOM and FOD. The species with most elevated VI were Psychotria vellosiana Benth., Alsophila setosa Kaulf. and Guatteria australis A.St.- Hil. The species with elevated VI, for their considerable representation in the area, are important in the restoration of degraded riparian forests in the region. The species seedlings plantation should be planned observing the group successional of each species, planting pioneer and light-demanding climax species first (e.g. Psychotria vellosiana), followed by, after the shading of the area, shade-tolerant species (e.g. Alsophila setosa e Guatteria australis).